A workability-strength synergistically enhanced composite admixture for fly ash geopolymer and its preparation method and application
Patent Information
- Application Number
- CN202610742183.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-27
- Publication Date
- 2026-08-18
AI Technical Summary
然而,目前的粉煤灰地聚合物在常温施工条件下仍存在明显工程应用缺陷,制约其规模化推广:一方面,碱性激发剂自身粘度较高,导致地聚合物浆体初始流动度不佳,施工和易性难以满足现场浇筑、泵送等工艺要求;另一方面,常温环境下粉煤灰的碱激发溶出速率缓慢,地聚反应进程滞后,致使材料凝结硬化迟缓、早期强度发展不足,后期强度增长亦难以达到工程设计标准,大幅延长施工周期
本发明通过科学研究和实践检验,成功制备出工作性-强度协同增强的复合外加剂,可提高粉煤灰地聚合物的工作性能,促进其凝结和强度发展。本发明提供的复合外加剂原料易得,制备工艺步骤简单,易于大范围推广应用,并且成本低,应用广泛,具有良好的经济效益和社会效益。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of building materials technology, and particularly relates to a workability-strength synergistic enhancement composite admixture for fly ash geopolymers, its preparation method and application. Background Technology
[0002] Fly ash geopolymer is a novel inorganic cementitious material formed through geopolymerization under the action of an alkaline activator, using fly ash as the main raw material. This material eliminates the need for high-temperature calcination of cement clinker and significantly reduces carbon emissions and energy consumption, while simultaneously achieving efficient resource utilization of large quantities of industrial solid waste. Furthermore, it possesses excellent corrosion resistance, high-temperature resistance, and heavy metal curing ability, demonstrating broad application prospects in road engineering, building structures, and hazardous waste treatment, and has become a key research and development direction in the field of low-carbon building materials. However, current fly ash geopolymers still exhibit significant engineering application defects under normal temperature construction conditions, hindering their large-scale promotion: on the one hand, the high viscosity of the alkaline activator results in poor initial fluidity of the geopolymer slurry, making it difficult to meet the requirements of on-site pouring and pumping processes; on the other hand, the slow alkali-activated dissolution rate of fly ash at normal temperature delays the geopolymerization process, leading to slow material setting and hardening, insufficient early strength development, and difficulty in achieving the required strength in later stages, significantly extending the construction cycle.
[0003] In existing technologies, conventional water-reducing agents are often added to improve the workability of fly ash geopolymers. However, due to the unique chemical environment of the alkali-activated system—characterized by high alkalinity and high ionic strength—the dispersion effect of conventional water-reducing agents is limited, and their improvement on fluidity is not significant. Furthermore, the incorporation of water-reducing agents interferes with the alkali-activated reaction process, disrupting the compactness of the geopolymer gel network structure, leading to a significant decrease in the strength of the hardened slurry. Experimental data show that adding 0.4% naphthalene-based water-reducing agent can improve fluidity by approximately 10%, but the 28-day compressive strength can decrease by more than 15%. Therefore, in traditional technologies, the improvement in the workability of fly ash geopolymers is limited and significantly sacrifices their mechanical properties. This performance bottleneck severely restricts their engineering application.
[0004] Therefore, how to provide a method to synergistically improve the workability and mechanical strength of fly ash geopolymer and solve the problem of mutual constraints between construction performance and structural performance is a technical problem that urgently needs to be solved by those skilled in the art. Summary of the Invention
[0005] To address the aforementioned technical problems, this invention proposes a workability-strength synergistic enhancement composite admixture for fly ash geopolymers, its preparation method, and its application.
[0006] To achieve the above objectives, the present invention provides the following technical solution: A workability-strength synergistic reinforcing composite admixture for fly ash geopolymers, comprising the following raw materials in parts by weight: 40-60 parts water-reducing agent, 15-25 parts Lewis acid, 5-10 parts low-gravity minerals, and 20-30 parts dispersing enhancer.
[0007] Preferably, the water-reducing agent is a naphthalene-based water-reducing agent or a melamine water-reducing agent.
[0008] Preferably, the water-reducing agent has a water reduction rate of not less than 25%.
[0009] Preferably, the Lewis acid is one of borax, barium nitrate, or zinc borate.
[0010] Preferably, the low-gravity mineral is fluorite powder.
[0011] Preferably, the mass fraction of CaF2 in the fluorite powder is not less than 80%.
[0012] Preferably, the dispersion enhancer is micron-sized calcium carbonate.
[0013] Preferably, the average particle size of the micron-sized calcium carbonate is 1-10 μm.
[0014] Beneficial Effects: The composite admixture provided by this invention achieves simultaneous improvement in the flowability and strength of fly ash geopolymers through the synergistic effect of two types of functional components (flowability-enhancing components and strength-enhancing components). The flowability-enhancing components include a naphthalene-based water-reducing agent, Lewis acid-borax, and low-attraction mineral-fluorite powder. These three components work synergistically to exert a water-reducing effect through a triple mechanism of electrostatic repulsion, complexation solubilization, and lubrication / friction reduction. Specifically, the naphthalene-based water-reducing agent forms an electric double layer on the surface of soil particles using sulfonic acid groups, generating electrostatic repulsion for dispersion; borax, as a Lewis acid, can react with OH- in a highly alkaline environment. - Complexation stabilizes the slurry pH and forms a coordination structure with the water-reducing agent molecules, inhibiting their decomposition and failure under alkaline conditions. Fluorite powder, with its low surface energy, creates a ball-bearing lubrication effect between particles, reducing friction within the slurry. The three components work synergistically to effectively overcome the shortcomings of using water-reducing agents alone, such as insufficient water-reducing capacity, easy decomposition under alkaline conditions, and poor water-reducing durability. The strength-enhancing component is micron-sized calcium carbonate, whose core role is manifested in both nucleation induction and pore filling effects. Specifically, micron-sized calcium carbonate acts as an early hydration nucleus, lowering the nucleation barrier to accelerate the formation of hydration products, shortening setting time, and improving early strength. Simultaneously, its micron-sized particles can fill the micropores of fly ash geopolymers, optimizing the pore structure and improving density and later strength.
[0015] In addition, the average particle size of micron-sized calcium carbonate is 1-10 μm. Only within this range can the nucleation barrier be reduced to accelerate the generation of hydration products, shorten the setting time, and improve early strength. If the particle size is smaller than this range, the workability will be reduced due to the increased specific surface area, and the structural uniformity will be destroyed due to the agglomeration effect. If the particle size is larger than this range, the nucleation effect cannot be effectively exerted.
[0016] A method for preparing a workability-strength synergistic reinforcing composite admixture for fly ash geopolymers includes the following steps: Weigh out the water-reducing agent, Lewis acid, low-attraction mineral, and dispersing agent according to the raw material composition of the above composite admixture, and mix the water-reducing agent, Lewis acid, low-attraction mineral, and dispersing agent evenly to obtain the workability-strength synergistic reinforcing composite admixture for fly ash geopolymer.
[0017] Application of a workability-strength synergistic reinforcing composite admixture for fly ash geopolymers.
[0018] Preferably, the fly ash geopolymer comprises the following raw materials in mass fractions: 85 wt% fly ash, 15 wt% sodium hydroxide, and 15 wt% water.
[0019] Preferably, the composite admixture is 0.8-1.2% of the mass of the fly ash.
[0020] Compared with the prior art, the present invention has the following advantages and technical effects: Through scientific research and practical testing, this invention has successfully prepared a composite admixture that synergistically enhances workability and strength, improving the workability of fly ash geopolymers and promoting their coagulation and strength development. The composite admixture provided by this invention uses readily available raw materials, has a simple preparation process, is easy to promote and apply on a large scale, and is low in cost, widely applicable, and has good economic and social benefits. Detailed Implementation
[0021] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0022] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the present invention will be further described in detail below with reference to specific embodiments.
[0023] This invention discloses a workability-strength synergistic reinforcing composite admixture for fly ash geopolymers, comprising the following raw materials in parts by weight: 40-60 parts water-reducing agent, 15-25 parts Lewis acid, 5-10 parts low-gravity minerals, and 20-30 parts dispersing enhancer.
[0024] In a preferred embodiment, the water-reducing agent is a naphthalene-based water-reducing agent.
[0025] In a preferred embodiment, the water reduction rate of the naphthalene-based water-reducing agent is not less than 25%.
[0026] In a preferred embodiment, the Lewis acid is borax.
[0027] In a preferred embodiment, the low-gravity mineral is fluorite powder.
[0028] In a preferred embodiment, the mass fraction of CaF2 in the fluorite powder is not less than 80%.
[0029] In a preferred embodiment, the dispersion enhancer is micron-sized calcium carbonate.
[0030] In a preferred embodiment, the average particle size of the micron-sized calcium carbonate is 1-10 μm.
[0031] This invention also discloses a method for preparing a workability-strength synergistic reinforcing composite admixture for fly ash geopolymers, comprising the following steps: According to the above-mentioned composite admixture raw material composition, weigh out the water-reducing agent, Lewis acid, low-attraction mineral and dispersing agent, mix the water-reducing agent, Lewis acid, low-attraction mineral and dispersing agent evenly to obtain the workability-strength synergistic reinforcing composite admixture for fly ash geopolymer.
[0032] This invention also discloses the application of a workability-strength synergistic reinforcing composite admixture for fly ash geopolymers in fly ash geopolymers.
[0033] In a preferred embodiment, the fly ash geopolymer comprises the following raw materials by mass fraction: Fly ash 85wt%, sodium hydroxide 15wt%, water 15wt%.
[0034] In a preferred embodiment, the composite additive is 0.8-1.2% of the mass of the fly ash, more preferably 0.8%.
[0035] Unless otherwise specified, all raw materials used in the embodiments of this invention were purchased through commercial channels; Among them, the water reduction rate of naphthalene-based water-reducing agents is 26%; The mass fraction of CaF2 in fluorite powder is 85%; The median particle size of micron-sized calcium carbonate is 3.56 µm; Unless otherwise specified, room temperature or normal temperature in the embodiments of the present invention refers to 20-30℃.
[0036] In the embodiments of this invention, unless otherwise specified, "parts" refers to "parts by mass".
[0037] Example 1 A workability-strength synergistic reinforcing composite admixture for fly ash geopolymers, comprising the following raw materials in parts by weight: 40 parts of water-reducing agent (naphthalene-based water-reducing agent), 25 parts of Lewis acid (borax), 10 parts of low-gravity mineral (fluorite powder), and 25 parts of dispersing enhancer (micron-sized calcium carbonate).
[0038] A method for preparing a workability-strength synergistic reinforcing composite admixture for fly ash geopolymers includes the following steps: Mix the above raw materials evenly to obtain a workability-strength synergistic enhancement composite admixture for fly ash geopolymer.
[0039] Example 2 A workability-strength synergistic reinforcing composite admixture for fly ash geopolymers, comprising the following raw materials in parts by weight: 50 parts of water-reducing agent (naphthalene-based water-reducing agent), 20 parts of Lewis acid (borax), 8 parts of low-gravity mineral (fluorite powder), and 22 parts of dispersing enhancer (micron-sized calcium carbonate).
[0040] A method for preparing a workability-strength synergistic reinforcing composite admixture for fly ash geopolymers includes the following steps: Mix the above raw materials evenly to obtain a workability-strength synergistic enhancement composite admixture for fly ash geopolymer.
[0041] Example 3 A workability-strength synergistic reinforcing composite admixture for fly ash geopolymers, comprising the following raw materials in parts by weight: 60 parts of water-reducing agent (naphthalene-based water-reducing agent), 15 parts of Lewis acid (borax), 5 parts of low-gravity mineral (fluorite powder), and 20 parts of dispersing enhancer (micron-sized calcium carbonate).
[0042] A method for preparing a workability-strength synergistic reinforcing composite admixture for fly ash geopolymers includes the following steps: Mix the above raw materials evenly to obtain a workability-strength synergistic enhancement composite admixture for fly ash geopolymer.
[0043] Example 4 A workability-strength synergistic reinforcing composite admixture for fly ash geopolymers, comprising the following raw materials in parts by weight: 60 parts water-reducing agent (melamine water-reducing agent), 15 parts Lewis acid (barium nitrate), 5 parts low-gravity mineral (fluorite powder), and 20 parts dispersing enhancer (micronized calcium carbonate).
[0044] A method for preparing a workability-strength synergistic reinforcing composite admixture for fly ash geopolymers includes the following steps: Mix the above raw materials evenly to obtain a workability-strength synergistic enhancement composite admixture for fly ash geopolymer.
[0045] Example 5 A workability-strength synergistic reinforcing composite admixture for fly ash geopolymers, comprising the following raw materials in parts by weight: 60 parts of water-reducing agent (naphthalene-based water-reducing agent), 15 parts of Lewis acid (zinc borate), 5 parts of low-gravity mineral (fluorite powder), and 20 parts of dispersing enhancer (micron-sized calcium carbonate).
[0046] A method for preparing a workability-strength synergistic reinforcing composite admixture for fly ash geopolymers includes the following steps: Mix the above raw materials evenly to obtain a workability-strength synergistic enhancement composite admixture for fly ash geopolymer.
[0047] Comparative Example 1 An admixture that uses only a water-reducing agent (naphthalene-based water-reducing agent).
[0048] Comparative Example 2 An admixture that uses only a dispersant enhancer (micron-sized calcium carbonate).
[0049] Comparative Example 3 An admixture that uses only Lewis acid (borax).
[0050] Comparative Example 4 An additive that uses only low-gravity minerals (fluorite powder).
[0051] Comparative Example 5 A composite admixture, differing from Example 1 only in that it does not include a dispersing enhancer, and specifically comprises the following raw materials in parts by weight: 40 parts water-reducing agent (naphthalene-based water-reducing agent), 25 parts Lewis acid (borax), and 10 parts low-gravity mineral (fluorite powder).
[0052] A method for preparing a composite admixture includes the following steps: Mix the above raw materials evenly to obtain the composite additive.
[0053] Application Example 1 The application of a workability-strength synergistic reinforcing composite admixture for fly ash-based polymers in fly ash-based polymers includes the following steps: The composite admixture prepared in Example 1, with 0.8% fly ash by weight, was incorporated into the raw materials of the fly ash-based polymer. The fly ash-based polymer comprised the following raw materials by weight: 85 wt% fly ash, 15 wt% sodium hydroxide, and 15 wt% water. After thorough mixing, the mixture was poured and cured for 28 days at 20±3℃ and 60±5% RH to obtain the fly ash-based polymer.
[0054] Application Example 2 The only difference from Application Example 1 is that the composite admixture prepared in Example 1 is replaced with an equal mass of the composite admixture prepared in Example 2, while the other process steps and parameters are the same as in Application Example 1.
[0055] Application Example 3 The only difference from Application Example 1 is that the composite admixture prepared in Example 1 is replaced with an equal mass of the composite admixture prepared in Example 3, while the other process steps and parameters are the same as in Application Example 1.
[0056] Application Example 4 The only difference from Application Example 1 is that the composite admixture prepared in Example 1 is replaced with an equal mass of the composite admixture prepared in Example 4, while the other process steps and parameters are the same as in Application Example 1.
[0057] Application Example 5 The only difference from Application Example 1 is that the composite admixture prepared in Example 1 is replaced with an equal mass of the composite admixture prepared in Example 5, while the other process steps and parameters are the same as in Application Example 1.
[0058] Comparative Application Example 1 The only difference from Application Example 1 is that the composite admixture prepared in Example 1 is replaced with an equal mass of the admixture in Comparative Example 1, while the other process steps and parameters are the same as in Application Example 1.
[0059] Comparative Application Example 2 The only difference from Application Example 1 is that the composite admixture prepared in Example 1 is replaced with an equal mass of the admixture in Comparative Example 2, while the other process steps and parameters are the same as in Application Example 1.
[0060] Comparative Application Example 3 The only difference from Application Example 1 is that the composite admixture prepared in Example 1 is replaced with an equal mass of the admixture in Comparative Example 3, while the other process steps and parameters are the same as in Application Example 1.
[0061] Comparative Application Example 4 The only difference from Application Example 1 is that the composite admixture prepared in Example 1 is replaced with an equal mass of the admixture in Comparative Example 4, while the other process steps and parameters are the same as in Application Example 1.
[0062] Comparative Application Example 5 The only difference from Application Example 1 is that the composite admixture prepared in Example 1 is replaced with an equal mass of the composite admixture in Comparative Example 5, while the other process steps and parameters are the same as in Application Example 1.
[0063] Comparative Application Example 6 The only difference from Application Example 1 is that the composite admixture prepared in Example 1 is not included; all other process steps and parameters are the same as in Application Example 1.
[0064] Technical effects: The fluidity, setting time, and compressive strength of the fly ash-based polymer materials prepared in Application Examples 1-3 and Comparative Application Examples 1-6 were tested.
[0065] The fluidity is determined in accordance with GB / T 8077-2023 "Test Method for Homogeneity of Concrete Admixtures"; The setting time is in accordance with the "Standard Consistency Water Requirement, Setting Time and Soundness Test Methods for Cement" (GB / T 1346). The compressive strength is tested according to the "Test Method for Strength of Cement Mortar (ISO Method)" (GB / T 17671).
[0066] The results are shown in Table 1: Table 1 Properties of polymer materials based on fly ash As can be seen from Table 1, compared with Comparative Application Example 6 without additives, the composite additives prepared in Examples 1-3 of this invention can improve the fluidity, shorten the setting time, and increase the compressive strength of fly ash geopolymers. Furthermore, the raw materials in this invention exhibit synergistic effects, especially the water-reducing agent, Lewis acid, and low-attraction minerals, which work synergistically to exert a water-reducing effect through a triple mechanism of electrostatic repulsion, complexation solubilization, and lubrication / friction reduction.
[0067] The water-reducing agent in this invention provides a dispersing effect, releasing encapsulated water to improve fluidity; Lewis acids and low-attraction minerals optimize particle packing density through filling effects and potential regulation; the reinforcing agent accelerates gel formation and enhances structural compactness through nucleation induction and polymerization catalysis. When these four components are combined, the retarding side effect of the water-reducing agent is offset by the reinforcing agent-Lewis acid combination. At the same time, each component forms functional complementarity and synergistic amplification in terms of fluidity, setting control, and strength development, ultimately achieving comprehensive performance optimization of "high fluidity, moderate setting, and high strength".
[0068] The above are merely preferred embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.
Claims
1. A workability-strength synergistic reinforcing composite admixture for fly ash geopolymers, characterized in that, The ingredients include the following parts by weight: 40-60 parts water-reducing agent, 15-25 parts Lewis acid, 5-10 parts low-gravity minerals, and 20-30 parts dispersing enhancer.
2. The workability-strength synergistic reinforcing composite admixture for fly ash geopolymers according to claim 1, characterized in that, The water-reducing agent is a naphthalene-based water-reducing agent or a melamine water-reducing agent.
3. The workability-strength synergistic reinforcing composite admixture for fly ash geopolymers according to claim 2, characterized in that, The water-reducing agent has a water reduction rate of not less than 25%.
4. The workability-strength synergistic reinforcing composite admixture for fly ash geopolymers according to claim 1, characterized in that, The Lewis acid is one of borax, barium nitrate, or zinc borate.
5. The workability-strength synergistic reinforcing composite admixture for fly ash geopolymers according to claim 1, characterized in that, The low-gravity mineral is fluorite powder.
6. The workability-strength synergistic reinforcing composite admixture for fly ash geopolymers according to claim 5, characterized in that, The mass fraction of CaF2 in the fluorite powder is not less than 80%.
7. The workability-strength synergistic reinforcing composite admixture for fly ash geopolymers according to claim 1, characterized in that, The dispersion enhancer is micron-sized calcium carbonate.
8. The workability-strength synergistic reinforcing composite admixture for fly ash geopolymers according to claim 7, characterized in that, The average particle size of the micron-sized calcium carbonate is 1-10 μm.
9. A method for preparing a workability-strength synergistic reinforcing composite admixture for fly ash geopolymers, characterized in that, Includes the following steps: According to any one of claims 1-8, the raw materials of the composite admixture are weighed as follows: water-reducing agent, Lewis acid, low-attraction mineral and dispersing agent. The water-reducing agent, Lewis acid, low-attraction mineral and dispersing agent are mixed evenly to obtain the workability-strength synergistic reinforcing composite admixture for fly ash geopolymer.
10. The application of a composite admixture as described in any one of claims 1-8 in fly ash geopolymers.